How clothing personalities of selected female high school students reflect Filipino values - Roxas, Cristopher A. (College of Home Economics, University of the Philippines Diliman, 2014)
Abstract Clothing is a mirror of a person?s true self ? a prism of the persona that she or he wants other people to see. It influences how people mould and represent their identities as they manage their appearances; how they interact with other people, and how they are influenced by the cultures and times in which they live in. Adolescence is an epoch in the life of a person which is filled with many transitions. A time to grow physically, to mature emotionally, to discover new knowledge, and to seek one?s self. In the process of molding their identities, they make sense of their own values and beliefs, relationship expectations, and goals in life. This study is focused on five clothing personalities ? artsy, classic, romantic, sporty and trendy, of selected female high school students, in relation to the Filipino values (damdamin, dangal, kapwa, pagpapahalaga sa pamilya and paggawa) that are significant to them. Descriptive research design was used for the study. A picture survey and questionnaire developed by the researcher were used to determine the respondents? clothing personalities and to yield quantifiable measures on the Filipino values they closely identify with. In the questionnaire, the Filipino values were translated into clothing behavior to create a direct correlation between values and clothing. Purposive sampling method was used, as the researcher intentionally selected the school and the respondents for the study. A sample size of 81 respondents, which is ninety four percent (94%) of the entire female student population of the senior high school level, was used in the study. Establishing his or her own identity is important for an adolescent. The clothes that they wear serve as a medium in which teenagers can show their individuality. The study revealed which clothing personalities did the selected female high school students identified with, and which Filipino values were most and least significant to them.